Prevalent North Atlantic Deep Water during the Last Glacial Maximum and Heinrich Stadial 1 - Blaser, Patrick; Waelbroeck, Claire; Thornalley, David J. R.; Lippold, Jörg; Pöppelmeier, Frerk; Kaboth-Bahr, Stefanie; Repschläger, Janne; Jaccard, Samuel (Nature geoscience, 2025)
Deep ocean circulation modulated glacial-interglacial climates through feedbacks to the carbon cycle and energy distribution. Past work has suggested that contraction of well-ventilated North Atlantic Deep Water during glacial times facilitated carbon storage in the deep ocean and drawdown of atmospheric CO2 levels. However, the spatial extent and properties of different water masses remain uncertain, in part due to conflicting palaeoceanographic proxy reconstructions. Here we combine five independent proxies to increase confidence and reconstruct Atlantic deep water distributions during the Last Glacial Maximum (around 21 thousand years ago) and the following Heinrich Stadial 1—a time when massive ice rafting in the North Atlantic interfered with deep water formation and caused global climate shifts. We find that North Atlantic Deep Water remained widespread in both periods, although its properties shifted from a cold, well-ventilated mode to a less-ventilated, possibly warmer, mode. This finding implies a remarkable persistence of deep water formation under these cold boundary conditions, sustained by compensation between the two formation modes. Our constraints provide an important benchmark for evaluating Earth system models, which can enhance confidence in future climate projections.
Online verfügbar: 06. Mai 2025
Gesehen am 06.11.2025